Dari Domestik ke Publik: Sejarah Pendidikan Kejuruan Perempuan dari Waktu ke Waktu - Mrr Ratna Endang Widuatie; Zellica Vanudia Amundari; Retno Winarni; Nurhadi Sasmita; Dewi Salindri (Yayasan Literasi Sains Indonesia, 2023)
Vocational education is a type of education that has always been one of the main focuses of the government in each period. Historically, vocational education for women in Indonesia was pioneered by two major figures, namely Kartini and Dewi Sartika in the early 20th century. Women's vocational education has undergone changes in line with demands for gender equality due to increasingly democratic socio-cultural conditions in Indonesia. This causes the diminishing differences in the roles of women and men in social roles. Women no longer only struggle in the domestic sphere as was the case with Kartini and Dewi Sartika, but also in the public sphere. This article examines the historical journey of women's vocational education and its dynamics starting from the thoughts of Kartini and Dewi Sartika, the Old Order, the New Order, and the Reformation. The argument put forward is that these two figures pioneered the birth of vocational education for women in Indonesia, so it is necessary to analyze whether there are differences in women's vocational education from time to time with their thoughts and what causes these changes.